Sejarah Perkembangan Islam di Pulau Lombok pada Abad Ke-17 - Basarudin Basarudin (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2019)
This paper describes the history of the development of islam in Lombok in the 17 thcentury, showing that the island of Lombok is one of the places where Islam carried out by Sunan Prapen from East Java. The history of the spread of Islam is very interesting to study in the region bicause some buildings show that Islam has spread very quickly. Since Islam entered the Island of Lombok which began around the 17 th century AD was brought from South Sulawesi, and distributed through the island of Sumbawa. After the arrival of Islam the teachings have not been maximally applied on the island of Lombok. This can be seen in the development of Islamic teachings in Lima and the teachings of Islam of Telu Time until now, which are still developing, such as in Bayan and Lingsar.